Gestures of greeting in the culture of communication in the south of Kazakhstan - Narozhnaya, Valentina D.; Kadeyeva, Mayra I.; Kanayeva, Lazzat S. (The New Research of Tuva, 2025)
The article analyzes the ethnocultural features of nonverbal behavior characteristic of the Kazakhs, the titular ethnic group of Kazakhstan, within the multicultural environment of the country’s southern regions. The source base includes information on nonverbal forms of greeting from ethnographic literature and dictionaries, whose usage was verified through the author’s observations and the results of a web survey of residents (September 2024). The study results indicate that the nonverbal behavior of contemporary Kazakhs continues to adhere to traditional etiquette norms. Gender-specific aspects of greetings and communication are also maintained. However, in practice, there is a diversity of forms reflecting the rich experience of multicultural interaction. General communicative greeting gestures function as situationally neutral and align in both form and meaning.